The nickel ion removal prediction model from aqueous solutions using a hybrid neural genetic algorithm - Hoseinian, Fatemeh Sadat; Rezai, Bahram; Kowsari, Elaheh (Journal of environmental management, 2017)
Prediction of Ni(II) removal during ion flotation is necessary for increasing the process efficiency by suitable modeling and simulation. In this regard, a new predictive model based on the hybrid neural genetic algorithm (GANN) was developed to predict the Ni(II) ion removal and water removal during the process from aqueous solutions using ion flotation. A multi-layer GANN model was trained to develop a predictive model based on the important effective variables on the Ni(II) ion flotation. The input variables of the model were pH, collector concentration, frother concentration, impeller speed and flotation time, while the removal percentage of Ni(II) ions and water during ion flotation were the outputs. The most effective input variables on Ni(II) removal and water removal were evaluated using the sensitivity analysis. The sensitivity analysis of the model shows that all input variables have a significant impact on the outputs. The results show that the proposed GANN models can be used to predict the Ni(II) removal and water removal during ion flotation. •A new predictive model based on GANN is developed to predict Ni(II) removal.•Ni(II) removal is sensitive to impeller speed, pH, collector concentration and time.•The water removal during ion flotation is more sensitive to flotation time and pH.•The new proposed GANN models has relative superiority to ANN models.